2018
DOI: 10.1242/jcs.213587
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome enlargement during inhibition of the lipid kinase PIKfyve proceeds through lysosome coalescence

Abstract: Lysosomes receive and degrade cargo from endocytosis, phagocytosis and autophagy. They also play an important role in sensing and instructing cells on their metabolic state. The lipid kinase PIKfyve generates phosphatidylinositol-3,5-bisphosphate to modulate lysosome function. PIKfyve inhibition leads to impaired degradative capacity, ion dysregulation, abated autophagic flux and a massive enlargement of lysosomes. Collectively, this leads to various physiological defects, including embryonic lethality, neurod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
164
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(188 citation statements)
references
References 82 publications
24
164
0
Order By: Relevance
“…These results confirmed that loss of PIKfyve activity, and consequent diminished PI(3,5)P2 synthesis, caused accumulation of endosomes and inhibition of lysosomal formation in osteoclasts. Our results are consistent with previous reports in various cells where, if PIKfyve is inhibited, membrane recycling is disrupted and vesicles become massively enlarged, cells have impaired degradative capacity, ion dysregulation, and abated autophagic flux resulting in different physiological defects and overt inflammation . Upon PIKfyve inhibition, fewer but enlarged endo/lysosomes were formed, suggesting endo/lysosome fusion was being favored over fission and that this imbalance resulted in endo/lysosome enlargement …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirmed that loss of PIKfyve activity, and consequent diminished PI(3,5)P2 synthesis, caused accumulation of endosomes and inhibition of lysosomal formation in osteoclasts. Our results are consistent with previous reports in various cells where, if PIKfyve is inhibited, membrane recycling is disrupted and vesicles become massively enlarged, cells have impaired degradative capacity, ion dysregulation, and abated autophagic flux resulting in different physiological defects and overt inflammation . Upon PIKfyve inhibition, fewer but enlarged endo/lysosomes were formed, suggesting endo/lysosome fusion was being favored over fission and that this imbalance resulted in endo/lysosome enlargement …”
Section: Discussionsupporting
confidence: 92%
“…PIKfyve has multiple roles, for example, in the conversion of early endo/phagosomes into mature lysosomes, lysosomal acidification, trafficking to late endosomes/lysosomes, and interleukin‐12 secretion in monocyte‐derived dendritic cells. In addition, this kinase plays a key role in T‐cell activation and in metastasis, and it has emerged as a potential target for treating solid tumors because it promotes cancer cell migration and invasion…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure E,F, the lysosomes were significantly enlarged in PIPKIγi5 knockdown cells compared with those in control cells. Enlarged lysosomes always indicate impaired lysosomal degradative capacity and lysosome dysfunction . This is consistent with the reduction in hydrolase sorting to lysosomes (Figure C).…”
Section: Resultssupporting
confidence: 80%
“…Because of THZ-P1-2's high potency on PIKfyve in the biochemical context, we took a step further to investigate its cellular activity on PIKfyve in a vacuolar enlargement assay. THZ-P1-2 produced the established PIKfyve-inhibitory phenotype in Vero cells only at a high concentration of 10 M, 1000 x that of positive control apilimod (Cai et al, 2013;Choy & Saffi et al, 2018;Sharma & Guardia et al, 2018) which causes substantial vacuolar enlargement at 10 nM ( Fig. S3D), but failed to show inhibition of PIKfyve at 1 M.…”
Section: Kinase Selectivity and Cellular Target Engagement By Thz-p1-2mentioning
confidence: 94%